고 비시지 접종률 상태에서 초등학생들의 투베르쿨린 조사를 통한 감염률 추정 조사 - 김희진; Hee Jin Kim; 오수연; Soo Yeon Oh; 이진범; Jin Bum Lee; 박윤성; Yun Sung Park; 류우진; Woo Jin Lew (Tuberculosis and respiratory diseases, 2008)
연구배경: 결핵 감염률은 결핵 실태를 파악하기 위한 기본 지표임에도 불구하고 1995년 전국실태조사를 마지막으로 실시되지 못하고 2000년 결핵정보감시체계로 대체되었다. 비시지 접종률이 높은 현 상황에서 무반흔자를 대상으로 한 감염률 조사는 실행이 어려우며 비시지 접종자를 대상으로 투베르쿨린 조사에 대한 비시지 영향 분석과 비시지 반흔과 상관없는 결핵 감염률 조사가 필요하다. 방법: 2006년에 전국 초등학교 1학년생들을 대상으로 각 시도별 아동 수를 추계한 후 학교를 대상으로 단면조사 연구를 하였다. 총 대상자 수는 40개 학교의 5,148명이 비례할당법으로 선정, 조사되었다. 투베르쿨린 검사는 2단위의 PPD RT 23 0.1 ml를 좌측 전박에 피내 주사한 후 48∼72시간 후에 가장 긴 횡직경을 측정하였다. 비시지 반흔에 대해서도 각각 조사하였다. 결과: 비시지 무반흔자는 6.3%였다. 평균 경결 크기는 0 mm 반응자 1,882명(46.8%)를 포함하여 3.7±4.4 mm였다. 결핵 감염률은 10 mm 이상을 양성 반응으로 했을 때 10.9% (439명)였다. 연간결핵감염위험률은 평균 연령을 6세로 하여 1.91%였다. 결핵 감염률은 비시지 반흔유무에 따른 유의한 차이는 없었다[11.2% vs. 7.6% (OR:1.54, 95% CI: 0.98∼2.43)]. 16 mm를 정점으로 한 거울 영상법으로는 감염률과 연간결핵감염위험률이 각각 2.4%와 0.4%였다. 결론: 결핵 감염률과 연간결핵감염위험률은 기존 방법으로 할 경우 높은 비시지 접종률로 인해 높게 나타났다. 결핵 감염률이 높지 않은 국가에서는 거울영상법이 두 지표를 추정하는데 보다 더 적합한 것으로 보인다. Background: Although the prevalence of tuberculosis infections (PTBI) is one of the basic epidemiologic indices, no survey has been carried out since 1995 because the nation-wide tuberculosis prevalence survey was changed to a surveillance system. Subjects without a BCG scar are examined in a tuberculin survey. However, it is very difficult to select these subjects under high vaccination coverage. It is important to evaluate the impact of BCG vaccinations on the tuberculin response and estimate the PTBI regardless of the BCG vaccination status. Methods: A nation-wide, school-based cross-sectional tuberculin survey was carried out among first graders in elementary school in 2006. A total of 5,148 children in 40 schools were selected by quota sampling. Tuberculin testing with 0.1 ml of two tuberculin units of PPD RT23 was carried out on 4,018 children. The maximum transverse diameter of induration was measured 48 to 72 hours later. The presence of a BCG scar was checked separately. Results: There were no BCG scars in 6.3% of the subjects. The mean induration size of tuberculin testing was 3.7±4.4 mm, which included 1,882 (46.8%) subjects with an induration size of 0 mm. The PTBI was 10.9% (439 subjects) using a cut-off point of ≥10 mm (conventional method). The annual risk of tuberculosis infections (ARTI) was 1.9% when the mean age of the subjects was assumed to be 6 years. There was no difference in the PTBI according to the presence or absence of a BCG scar [11.2% vs 7.6% (OR: 1.54, 95% CI: 0.98∼2.43)]. Using a mirror image technique with 16 mm as the cut-off point, the PTBI and ARTI had decreased to 2.4% and 0.4% respectively. Conclusion: PTBI and ARTI, as estimated by conventional methods, appear to be high among BCG vaccinated children. A mirror image technique is more suitable for estimating the indices in a country with an intermediate burden of tuberculosis than the conventional method. (Tuberc Respir Dis 2008;65:269-276)